2011
DOI: 10.1007/s00410-011-0697-1
|View full text |Cite
|
Sign up to set email alerts
|

Li isotopes and trace elements as a petrogenetic tracer in zircon: insights from Archean TTGs and sanukitoids

Abstract: We report d 7 Li, Li abundance ([Li]), and other trace elements measured by ion probe in igneous zircons from TTG (tonalite, trondhjemite, and granodiorite) and sanukitoid plutons from the Superior Province (Canada) in order to characterize Li in zircons from typical Archean continental crust. These data are compared with detrital zircons from the Jack Hills (Western Australia) with U-Pb ages greater than 3.9 Ga for which parent rock type is not known. Most of the TTG and sanukitoid zircon domains preserve typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(48 citation statements)
references
References 106 publications
1
46
0
1
Order By: Relevance
“…Large δ 7 Li variations in zircon were also observed by Bouvier et al (2012), who concluded that it reflected the signatures of the magma source materials.…”
Section: Isotopes In Zirconsmentioning
confidence: 78%
See 4 more Smart Citations
“…Large δ 7 Li variations in zircon were also observed by Bouvier et al (2012), who concluded that it reflected the signatures of the magma source materials.…”
Section: Isotopes In Zirconsmentioning
confidence: 78%
“…Lithium may substitute in a zircon lattice by coupling with trivalent REE and Y ions Hanchar et al, 2001;Ushikubo et al, 2008;Bouvier et al, 2012), and in this case, Li diffuses together with REE and Y, which will slow Li diffusivity by orders of magnitude. However, this mechanism has not been observed by current experimental studies (Cherniak and Watson, 2010;Trail et al, 2016), both of which reported fast Li diffusion in zircon.…”
Section: Experimental Perspectives On LI Diffusion In Zirconmentioning
confidence: 99%
See 3 more Smart Citations